2002
DOI: 10.1007/s11745-002-0901-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary conjugated linolenic acid in relation to CLA differently modifies body fat mass and serum and liver lipid levels in rats

Abstract: The present study compared the effect of dietary conjugated linolenic acid (CLNA) on body fat and serum and liver lipid levels with that of CLA in rats. FFA rich in linoleic acid, a-linolenic acid, CLA, or CLNA were used as experimental fats. Male Sprague-Dawley rats (4 wk old) were fed purified diets containing 1% of one of these experimental fats. After 4 wk of feeding, adipose tissue weights, serum and liver lipid concentrations, serum tumor necrosis factor (TNF)-alpha and leptin levels, and hepatic beta-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 50 publications
7
102
0
6
Order By: Relevance
“…However, several in vivo studies using 9c, 11t, 13t-CLN or bitter melon oil rich in this fatty acids have been reported. In addition to increase the antioxidant activity of blood and liver lipid in rats [10], 9c, 11t, 13t-CLN has also been reported to modulate the body fat and triglyceride metabolism in a manner that is different from CLA [19]. Although CLN increased serum and liver triglyceride level, it reduced the weight of perirenal and epididymal adipose tissue and enhanced the activity of b-oxidation in liver mitochondria and peroxisomes to a higher extent than CLA [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several in vivo studies using 9c, 11t, 13t-CLN or bitter melon oil rich in this fatty acids have been reported. In addition to increase the antioxidant activity of blood and liver lipid in rats [10], 9c, 11t, 13t-CLN has also been reported to modulate the body fat and triglyceride metabolism in a manner that is different from CLA [19]. Although CLN increased serum and liver triglyceride level, it reduced the weight of perirenal and epididymal adipose tissue and enhanced the activity of b-oxidation in liver mitochondria and peroxisomes to a higher extent than CLA [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increase the antioxidant activity of blood and liver lipid in rats [10], 9c, 11t, 13t-CLN has also been reported to modulate the body fat and triglyceride metabolism in a manner that is different from CLA [19]. Although CLN increased serum and liver triglyceride level, it reduced the weight of perirenal and epididymal adipose tissue and enhanced the activity of b-oxidation in liver mitochondria and peroxisomes to a higher extent than CLA [19]. Noguchi et al fed rats with bitter gourd oil (BGO) diets for 4 weeks and found occurrence of c9, t11-conjugated linoleic acid (c9,t11-CLA) in the liver of rats [26], and the conversion of c9,t11, t13-CLN to CLA by an enzymatic biohydrogenation in rat tissue was confirmed later [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects have been observed in another study in the same animal model. 94 Results of these studies suggest that reductions in fat mass due to CLA (or reduced food intake) are associated with reductions in leptin, which induces insulin resistance.…”
Section: Cla Induces Insulin Resistancementioning
confidence: 99%
“…The seed oils of pomegranate, catalpa, and pot marigold contain 83.0% punicic acid (9c,11t,13c-CLN), 42.3% catalpic acid (9t,11t,13c-CLN), and 62.2% calendic acid (8t,10t,12c-CLN), respectively (14). As for the biological activity of CLN, dietary CLN produced by alkaline isomerization of linolenic acid (LN) reduces fat content in the body (15). Purified punicic acid has a hypolipidemic effect (16).…”
Section: Introductionmentioning
confidence: 99%